Stent dislodgement in the distal left main coronary artery and its successful management with balloon crushing technique - Stajić Zoran (Vojnosanitetski Pregled)
Introduction. Stent entrapment and dislodgment in the coronary arteries is a rare but potentially fatal complication of percutaneous coronary intervention. Different retrival techniques of dislodged stents have previously been reported with high success rate but all of them are timeconsuming, so as not quite useful in hemodinamically unstable patient. Case report. A 59-year old female patient with acute ST-elevation myocardial infaction of anterior wall was admitted for primary percutanous coronary intervention. Unexpectedly, during intervention stent entrapment and dislodgement in the distal left main coronary artery occured followed by occlusive coronary dissection and compromisation of the coronary flow in the left descending coronary artery with a rapid hemodinamic deterioration. In order to reestablish coronary flow as soon as possible, the dislodged unexpanded stent was crushed against the wall with a balloon in the distal left main. It immediately restored coronary flow in the left descending coronary artery and rapidly improved the patients hemodinamics. Intervention was successfuly completed with totally four stents implanted in the left main, the osteoproxymal circumflex coronary artery and the osteo-proxymedial left descending coronary artery. Later postinterventional hospital course as well as the clinical and angiographic six month follow-up was uneventful. Conclusion. This case shows that percutaneous baloon crushing technique can be a safe and effective first option in management of dislodged and unexpanded stent in the left main coronary artery, particularly for a hemodynamically unstable patient.